Does tax evasion affect unemployment and educational choice? - Ann-Sofie Kolm; Birthe Larsen (Institute for Labour Market Policy Evaluation (IFAU), 2004)
To examine the macro economic effects of government tax and punishment policies, this paper develops a three-sector general quilibrium model featuring matching frictions, heterogenous abilities and an informal sector with tax evasion. The choice of education is determined endogenously. Job opportunities in an informal sector are available only to workers who choose not to acquire higher education. We find that increased punishment of informal activities increases the number of educated workers and reduces the number of unemployed workers. Characterizing the optimal tax and punishment system, we show that it is optimal to more than fully counteract the distortion created by the governments inability to tax the informal sector. The optimal choice of tax and punishment system, however, implies an inefficiently low stock of educated workers.
Keywords: H26; I21; J64; 330; Tax evasion; underground economy; education; matching; unemployment